2016
DOI: 10.1001/jamasurg.2015.4990
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Flexibility in Duty Hour Requirements for Surgical Trainees (FIRST) Trial Protocol

Abstract: clinicaltrials.org Identifier: NCT02050789.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 28 publications
0
71
0
Order By: Relevance
“…The study sample included general surgery residents in 117 general surgery residency programs in the U.S. and 151 affiliated hospitals that participated in the FIRST Trial. 7, 8 Programs were randomly assigned to either “Standard Policy,” which required adherence to all current ACGME duty hour requirements, or “Flexible Policy” in which the daily duty hour limits (e.g., 16 hours for interns and 28 hours for senior residents) and minimum time off between shift requirements (8 hours between daily shifts and 14 hours off after a 24-hour call) were waived through a formal waiver from the ACGME. All programs, regardless of study arm assignment, were required to adhere to the requirements regarding the 80-hour work week, one day off in seven, and call no more frequently than every third night.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study sample included general surgery residents in 117 general surgery residency programs in the U.S. and 151 affiliated hospitals that participated in the FIRST Trial. 7, 8 Programs were randomly assigned to either “Standard Policy,” which required adherence to all current ACGME duty hour requirements, or “Flexible Policy” in which the daily duty hour limits (e.g., 16 hours for interns and 28 hours for senior residents) and minimum time off between shift requirements (8 hours between daily shifts and 14 hours off after a 24-hour call) were waived through a formal waiver from the ACGME. All programs, regardless of study arm assignment, were required to adhere to the requirements regarding the 80-hour work week, one day off in seven, and call no more frequently than every third night.…”
Section: Methodsmentioning
confidence: 99%
“…8 The unit of analysis was at the resident level. We explored the inclusion of various resident and program level characteristics in the model such as gender, geography, and academic vs non-academic program status.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple North American medical commissions have advocated for duty hour circumscriptions including the Bell Commission, which instituted New York State's limit on resident work hours, the Institute of Medicine, the Accreditation Council for Graduate Medical Education (ACGME), and Canada's National Steering Committee on Resident Duty Hours. In 2003 and 2011, the ACGME placed constraints on labor hours by physicians in training mandating a maximum 80-hour work a week, dictating compulsory time off between shifts, and circumscribing on-call periods [14]. In developing the ACGME's 2011 directives, policy makers sought to enhance the safety of patients and to foster learning environments that nurture physicians' professional development by promoting resident respite, wellness, and empathy [7].…”
Section: Medical Commissions Advocate For Duty Hour Restrictionsmentioning
confidence: 99%
“…3,4 Current duty hour regulations were borne from concern that extreme resident fatigue posed a risk to patient safety. 5,6 After initial ACGME regulations for an 80-hour work week maximum in 2003, duty hours were further restricted in 2011 after the release of an Institute of Medicine report recommending shorter shift lengths for interns and residents.…”
mentioning
confidence: 99%
“…The methods have been described extensively elsewhere. 3 The FIRST trial authors concluded that flexible duty hour policies for surgical residents were noninferior to current ACGME duty hour policies for patient outcomes and resulted in similar resident satisfaction about their overall well-being and education quality. 12 Research to gauge resident and program director (PD) perceptions of duty hour requirements suggests that the 2011 restrictions drove resident dissatisfaction and delayed maturation of residents, brought about challenges surrounding the night float system, and decreased the surgical case volume for residents.…”
mentioning
confidence: 99%